Recent advances in managing triple-negative breast cancers - Bengala, Carmelo (Medicine Reports Ltd, 2009)
Triple-negative breast cancer (TNBC) has been recently recognized as an important subgroup of breast cancer with a distinct outcome and therapeutic approach compared with other breast cancer subgroups. Because TNBC is defined by the absence of a target (either hormone receptors or HER-2), conventional cytotoxic therapy is still the mainstay of treatment. This report focuses on the current state and recent advances in managing TNBC.